An Updated Review on the Chemistry, Biological Characteristics and Analytical Techniques of Dapagliflozin - Chaudhari, Ujwal; Sahu, Jagdish K.; Dande, Payal R. (Current Organocatalysis, 2023)
Background: Globally, type 2 diabetes mellitus (T2DM) prevalence is increasing. A patient must have lifetime therapy for diabetes to manage it and prevent any complications. There are many different medications that can be used to treat Type 2 diabetes. Still, almost all of them concentrate on the declining insulin sensitivity and secretion that are associated with the onset of the illness. Methods: There is growing interest in the development of innovative anti-diabetic medications that are not insulin-reliant because treatments with such insulin-dependent mechanisms of action usually lose their effectiveness over time. One such technique is the inhibition of renal glucose reuptake. Results: Dapagliflozin, the first line of selective sodium-glucose cotransporter 2 inhibitors that reduce renal glucose reabsorption, is currently being developed as a therapy for Type 2 diabetes. Numerous analytical techniques have been developed for its detection, measurement, and regular quality control procedures. Conclusion: This review deliberates a thorough discussion on the chemistry of Dapagliflozin, all of its pharmacological actions with analytical and bioanalytical analyses, and more information on the clinical trials.
Keywords: Antidiabetic